ECONOMICAL-MATHEMATICAL MODELS AS A TOOL OF SOLVING PRACTICAL TASKS - L. B. Shabanova; V. N. Kushnirenko (Russian Journal of Economics and Law)
In spite of the fact that economical-mathematical models are known as one of the efficient means of analysis, predicting and managing the economical processes, their practical application does not always ensure high accuracy and reliability of results. Consequently, there is a need to critically analyze the most well-known economic models, and to propose an algorithm of solving the topical problem of setting the balanced price of goods, which may become practically significant for entrepreneurs as a tool of solving this problem.